PENERAPAN PENDIDIKAN KARAKTER BERBASIS CIVIC CULTURE DA-LAM MENGURANGI KONFLIK ANTAR SISWA DI SD - Sri Hartati; Masniar, Debi Servinta Br Perangin-Angin; Rijal Sianturi, Dr Reh Bungana Beru Perangin-Angin,M.Hum (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Elementary school pupils' conflicts are a habitual occurrence in school life. Such conflicts frequently result from opinion disparity, rivalry in studies or external activities, emotional unreadiness, and shortage of knowledge regarding common values like tolerance, empathy, and cooperation. If not controlled, such conflicts may influence the classroom climate negatively, impede learning activities, and interfere with the students' character development. Therefore, schools need to implement strategic interventions that not only de-escalate conflict but also foster values that enable students to resolve conflict in a positive way. This study aims to explore the implementation of civic culture-based character education as a means of reducing interpersonal conflict among students at the elementary school level. The research used a qualitative descriptive research design with a case study approach. Data gathering was through observation in the classroom, semi-structured interviews from the teachers and students, and documentation of school events. Data analysis utilized Miles and Huberman's model of interactive analysis, which consists of data reduction, display of data, and conclusion drawing.